2022
DOI: 10.1158/0008-5472.can-22-2108
|View full text |Cite
|
Sign up to set email alerts
|

Dormant SOX9-Positive Cells Facilitate MYC-Driven Recurrence of Medulloblastoma

Abstract: Relapse is the leading cause of death in patients with medulloblastoma, the most common malignant pediatric brain tumor. A better understanding of the mechanisms underlying recurrence could lead to more effective therapies for targeting tumor relapses. Here, we observed that SOX9, a transcription factor and stem cell/glial fate marker, is limited to rare, quiescent cells in high-risk medulloblastoma with MYC amplification. In paired primary-recurrent patient samples, SOX9-positive cells accumulated in medullob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
(103 reference statements)
1
12
0
Order By: Relevance
“…The presence of DTC in the bone marrow has also been shown to be associated with a higher risk of clinically detectable breast cancer metastasis [ 39 , 40 ]. A similar finding has also been reported in cancer patients with colon liver metastases [ 41 ] and MYC-amplified high-risk medulloblastoma [ 42 ]. In short, findings discussed here suggest that QCCs may exist earlier than relapse and play a key role in tumor recurrence.…”
Section: Quiescent Cancer Cells Lead To Tumor Recurrencesupporting
confidence: 86%
See 1 more Smart Citation
“…The presence of DTC in the bone marrow has also been shown to be associated with a higher risk of clinically detectable breast cancer metastasis [ 39 , 40 ]. A similar finding has also been reported in cancer patients with colon liver metastases [ 41 ] and MYC-amplified high-risk medulloblastoma [ 42 ]. In short, findings discussed here suggest that QCCs may exist earlier than relapse and play a key role in tumor recurrence.…”
Section: Quiescent Cancer Cells Lead To Tumor Recurrencesupporting
confidence: 86%
“…They identified a similar main quiescence-associated transcription program between both tumors that underlined an upregulation in stemness, pro-metastatic, chemoresistance, and EMT-like pathways, e.g., KLF4 and ZEB2 [ 44 ]. Moreover, in addition to ki67 and p27, researchers also consider other markers to focus on specific proportions of QCCs, e.g., Yes and YAP [ 41 ] or SOX9 [ 42 ], revealing the diversity of QCCs across different conditions (e.g., primary site, distant metastatic site, cancer type, or specific genomic signature).…”
Section: Quiescent Cancer Cells Lead To Tumor Recurrencementioning
confidence: 99%
“…Conventional RNA sequencing was performed on GMYC ( n = 6) tumors that was compared to RNA sequences similarly generated on GTML ( n = 8) tumors 32 . When compared via cross-species analysis to other human childhood brain tumors, including glial or mixed glioneuronal tumors (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA from GMYC ( n = 6) tumor samples was sequenced through the Ion Proton TM Sequencer at the Uppsala Genome Center, SciLifeLab, Uppsala University. Raw RNA-seq reads GMYC, previously generated GTML tumors ( n = 7) 32 and new GTML tumors and Arf knockout cell lines and controls were aligned to the mouse mm9 genome assembly using the STAR aligner (v2.7.2b) 71 followed by an additional application of Bowtie (v2.3.4.3) 72 . The STAR mapping utilized a two-pass approach, with the first alignment pass designed to discover splice junctions, which were then utilized for an improved alignment in the second pass.…”
Section: Methodsmentioning
confidence: 99%
“…SOX9 is an important transcription factor located on chromosome 17q24. As a member of the SOX transcription factor family, SOX9 plays a key role in embryonic development and stem cell maintenance [3]. Shirian, et al veri ed that the protein level of SOX9 was up-regulated in 60 pairs of matched pituitary tumor tissues, and found that the high expression level of SOX9 was related to the invasive degree of growth hormone secreting pituitary adenoma patients and the formation of larger tumors [25].…”
Section: Discussionmentioning
confidence: 99%